Developing Science Teachers’ Understanding of Engineering Design Process through Workshop on Biomimicry for Green Design - Pongsophon, Pongprapan; Pinthong, Tanwarat; Lertdechapat, Kornkanok; Vasinayanuwatana, Thanika (Science Essence Journal, 2021)
This study aims to examine the effect of a training workshop about design-based learning integrated with biomimicry for sustainability on science teachers’ understanding of the engineering design process. Participants (N=30) were recruited from STEM high schools in the central part of Thailand. During the two-day intensive workshop, the participants attended a special lecture on biomimicry for product design and development, engaged in a design challenge, designed and presented lesson plans and obtained feedback, reflected on their workshop experience, and discussed possible challenges and issues in implementing design-based learning with biomimicry in their classroom contexts. The results indicate that most of the teachers already had a sound understanding of many essential features of the engineering design process. Nonetheless, the workshop could broaden and reinforce their knowledge. The participants learned the following during the workshop: a design challenge always has a problem; limitations need to be considered during the design process; innovators must work on prototypes and test and improve them before creating full-scale products; the design process is iterative and sometimes messy. Finally, implications on sustainability education and the development of 21st-century skills as well as some challenges and issues in school implementation are discussed.